O lúdico na aprendizagem e no desenvolvimento da criança com autismo - NEVES, Bruna Soares (2019)
Playfulness is essential for the child, as it favors their development in multiple abilities and functions in the cognitive, social, emotional and also motive. Since, Autism Spectrum Disorder (ASD) shows some alteration in the game, especially at the symbolic level. The intervention of this difficulty will directly affect the social and communicative area. Since play is an effective learning tool and vital part in the development of every individual, it is important to approach it in a broad way and adapted to the specific characteristics and needs of each child. Therefore, the objective of this research is to study the use of play in pedagogical practice, as an important element for the teaching-learning of children with autism. The games and games used in the room, in the development of children with ASD, help in the behavior of the child. In this way, to observe how the playful one manifests itself before its learning. The research presents a qualitative approach and the technique of data collection was participant observation. Thus, it is possible to verify that inclusive processes still have to be implemented in practice and that teachers still feel unprepared to receive students with atypical development. This whole educational process shows the importance and necessity of games and games to promote inclusion in general.